2016
DOI: 10.5547/01956574.37.2.zcse
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Economic Growth: The Stylized Facts

Abstract: We summarize what we know about energy and economic growth in a set of stylized facts. We combine analysis of a panel data set of 99 countries from 1971 to 2010 with analysis of some longer run historical data. Our key result is that over the last 40 years there has been a stable cross-sectional relationship between per capita energy use and income per capita with an elasticity of energy use with respect to income of less than unity. This implies that energy intensity has tended to decrease in countries that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
125
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 55 publications
23
125
3
3
Order By: Relevance
“…Their results point to evidence of weak decoupling but no sign that at high-income levels the income elasticity turns negative-no Kuznets curve behavior. Over the same period for 99 countries Csereklyei et al [6] find an income elasticity that is less than one. This Kuznets behavior, as illustrated in Fig.…”
Section: Energy-gdp Elasticitymentioning
confidence: 99%
“…Their results point to evidence of weak decoupling but no sign that at high-income levels the income elasticity turns negative-no Kuznets curve behavior. Over the same period for 99 countries Csereklyei et al [6] find an income elasticity that is less than one. This Kuznets behavior, as illustrated in Fig.…”
Section: Energy-gdp Elasticitymentioning
confidence: 99%
“…Marcotullio and Schulz (2007) showed that the USA was also an energy intensive economy compared with others at similar levels of GDP per capita. Using a larger historical database, Csereklyei et al (2016) find that, although they tend to broadly converge at high levels of per capita income, some (but certainly not all) economies did exhibit flat energy intensity trends in the long run. Interestingly, this evidence partially contrasts with a recent study which finds that present-day developing economies are experiencing higher energy intensities at the same per capita income levels (i.e., within the $3,500-$10,000 range) as present-day OECD countries did historically (van Bentham 2015).…”
Section: Transferability Of Historical Lessons To Future Patterns Of mentioning
confidence: 99%
“…Given that the efficiencies of energy technologies have improved dramatically over the last two hundred years 32 and played a role in declining energy intensities (that is, the energy use to GDP ratio) 33,34 , one study setout to identify whether currently developing economies are less energy-intensive than present day OECD countries, when they were at similar levels of economic development 35 . It identified three factors influencing their energy-intensities: more efficient technologies today; more exporting in developing economies today; and more consuming of energy-intensive bundles today.…”
Section: Locking-into Energy-intensive Systemsmentioning
confidence: 99%